Screening of phytochemicals, antioxidant activity, and in vivo safety profile of the hydroethanolic peel extract of Musa sapientum - Mishell Chantelle Mahora; Alex Kigundu; Rebecca Waihenya (Plant Trends, 2024)
Introduction: Banana peels can be utilized as nutraceuticals in the management of disease caused by oxidative stress, like any other plant material. It is therefore, important to understand the phytochemical constitute, antioxidant capacity and the safety profile of Musa sapientum variety Muraru peels. Aim of the study: The study identified the chemical composition of unripe and ripe Musa sapientum variety Muraru peels, along with its antioxidant capacity and evaluated the oral acute and sub-acute toxicity of Muraru peel hydroethanolic extracts. Materials and methods: Qualitative and quantitative phytochemical analyses were performed, GC-MS was used in the identification of bioactive compounds present. The DPPH total antioxidant activity was used to evaluate the scavenging percentage and IC50. Acute and sub-acute toxicity tests were done for Musa sapientum variety Muraru hydroethanolic peel extract. Hematology, biochemistry and relative organ weight were analyzed, with the sub-acute group organs were further analyzed for histopathology. Results: Flavonoids, tannins, phenols were found abundant in both unripe and ripe Muraru peels. GC-MS showed that the peels were rich in lipids, fatty acids and terpenoids. The unripe peels showed significant total antioxidant capacity. No significant difference (p> 0.05) was observed in hematology, biochemistry, relative organ weight compared to the normal controls. Histopathological examination of liver, lung, heart, kidney and spleen showed normal tissue orientation in all treated groups. Conclusion: Unripe and ripe Musa sapientum variety Muraru peels are both rich in various secondary metabolites which greatly influenced its antioxidant capacity. Toxicity profile showed that Muraru hydroethanolic peel extract are nontoxic. [Plant Trends 2024; 2(1.000): 1-15]